Effects of Physical Activity on Female and Male Fertility: A Literature Review - Syncerz, Natalia; Czajka, Katarzyna; Zadrożna, Katarzyna; Dryżałowski, Piotr; Steć, Sara; Wójcik, Bartłomiej; Borodacz, Julia; Czampiel, Martyna; Nawracaj, Michał; Bort, Julia (Journal of Education, Health and Sport, 2026)
Introduction: Infertility affects an estimated 60–80 million couples globally and represents a growing public health concern. Its etiology is multifactorial, with modifiable lifestyle and environmental factors playing a significant role. Among these, physical activity is increasingly recognized as a relevant contributor, although its precise impact on reproductive outcomes remains unclear. Promoting balanced, evidence-based strategies—including appropriate physical activity during the periconceptional period—should be considered a shared responsibility in preconception care. Objective: This review aims to synthesize current evidence on the role of physical activity in fertility, highlighting its relevance to both sexes. It discusses exercise types that support reproductive potential, contrasts them with potentially harmful modalities, and explores underlying physiological and cellular mechanisms. Conclusion: Couples planning pregnancy should appropriately adjust their lifestyle by engaging in moderate and regular physical activity suited to their individual capacity, while avoiding high-intensity or strenuous exercise. Infertility arises from both female and male factors, with each contributing to roughly half of all cases. High-intensity physical activity may impair fertility by contributing to menstrual cycle disturbances in women and reduced sperm quality in men. Both sexes have been shown to exhibit dysregulation of the hypothalamic–pituitary–gonadal axis under such conditions. Despite the abundance of literature on the subject, there is still a lack of conclusive evidence identifying the most beneficial type of physical activity for couples trying to conceive. Future research should focus on designing highly standardized studies that will serve as a foundation for clear and evidence-based lifestyle recommendations supporting reproductive health.